Determinants of organizational performance: a case of Punjab Police - Laeeq, Hood; Shahzad, Arfan; Sri Ramalu, Subramaniam; Fareed, Muhammad (Sukkur Institute of Business Administration, 2016)
In the last three decades, the security issues have been raised in the state of the Punjab (Pakistan) which ultimately leads to the breakdown of the country’s economy.However, the purpose of this paper is to determine the effect of the political interference on the performance of Punjab police (Pakistan) with the moderating role of organizational support.To elicit the findings, a total of 159 survey questionnaires were compiled from station house officers (SHOs) of Punjab police (Pakistan).Furthermore, this study has applied PLS-SEM technique to analyze the data. The findings reveal that a negatively significant effect of political interference on the performance of Punjab police (Pakistan).Moreover, the findings also showed the significant moderating effect of organizational support in the instance of political interference.